Two-dimensional spectral interferometry in the extreme-ultraviolet enabled by computational phase-stabilization - Hedewig, Lina; Kleine, Carlo; Wieder, Felix; Ott, Christian; Pfeifer, Thomas (Optics express, 2025)
In this paper, the concept of spectral interferometry is transferred to the extreme ultraviolet (XUV) by a two-fold approach. On the one hand, in addition to the frequency-resolved spectrogram, a spatial dimension is added to the analysis by tilting the two beams relative to each other for two-dimensional spectral interferometry (2DSI). On the other hand, computational phase stabilization exploits the stable phase relation between two spectral regions of the same pulse and allows for correcting for instabilities during post-processing, resulting in an effective interferometer stability of 1.06 as. The mutual benefit of those two aspects is demonstrated by the extraction of the spectral phase imprinted on a transmitted XUV pulse in the vicinity of the neon 2s2p63p absorption line.
Veröffentlicht: 6. November 2025
Gesehen am 23.01.2026